Membangun Website Organisasi Pencak Silat Berbasis Virtual Private Server (VPS) - Pebrianto, Debi; Khairil, Khairil; Asyari, Ahmad (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The development of information technology has encouraged organizations to utilize digital media as a means of promotion and communication. This study aims to build a professional, informative, and widely accessible pencak silat organization website through Virtual Private Server (VPS) infrastructure. The development methods used include system requirements planning, interface design, website implementation using the latest web technologies (such as HTML, CSS, JavaScript, and PHP), and VPS configuration for independent hosting. This website provides features such as an organization profile, activity gallery, latest news, online member registration, and a content management system that makes it easy for administrators to update information. The use of VPS provides flexibility in server management, better security, and more stable performance compared to shared hosting. The final result shows that the website built can function properly and meet the organization's needs in terms of digitalizing information and membership services. With this website, it is hoped that Pencak Silat organization can enhance its presence in the digital era and expand its communication reach with the public.